2013
DOI: 10.2298/tsci110630105z
|View full text |Cite
|
Sign up to set email alerts
|

A simulated study on the performance of diesel engine with ethanol-diesel blend fuel

Abstract: This paper describes the simulated study on atomization, wall-film formation, combustion and emission forming process of ethanol-diesel blend fuels in a high speed light duty diesel engine. The result shows that increased ethanol volume percentage of the blend fuels could improve atomization and reduce wall-film formation. However, in the meanwhile, with the increased ethanol volume percentage, low heat values of blend fuels decrease, while both total heat releases and cylinder pressures drop. By adding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…From the literature review, it is clear that most of the research work on ethanol has been done on blend with diesel [4][5][6][7][8][9] and [16][17][18]. Although many publications on dual fuel engines can be found in the literature, it seems that the topic has not been exhausted.…”
Section: Introductionmentioning
confidence: 99%
“…From the literature review, it is clear that most of the research work on ethanol has been done on blend with diesel [4][5][6][7][8][9] and [16][17][18]. Although many publications on dual fuel engines can be found in the literature, it seems that the topic has not been exhausted.…”
Section: Introductionmentioning
confidence: 99%
“…This could be explained by the delayed combustion of the pilot injection. By contrast, other authors [60] found that the higher the presence of ethanol in the blend, the lower the combustion noise, this being due to the decrease of the cylinder pressure and heat release rates. Heuser et al [61] demonstrated that high ethanol shares showed worse combustion noise at low load than at high load.…”
Section: Noise Emissionsmentioning
confidence: 70%
“…An active interest, shown in the last 5-7 years in the studies of integral characteristics of the interaction of colliding liquid drops in a gas medium, is conditioned by the main objective, namely to identify the key mechanisms and to search for the regimes of controlling these processes in many modern promising technologies, e.g., fuel combustion in IC engines [1][2][3], fire-fighting [4], pharmaceuticals production [5], application of aerosol systems to determine the level of air pollution [6], etc. The objects of such studies include both homogeneous and two, three and multi-component drops of solutions, slurries, and emulsions.…”
Section: Introductionmentioning
confidence: 99%